Regiocomplementary Synthesis of Fluorinated Bridged Biphenyls - Nemoto, Hiroyuki; Takubo, Keita; Shimizu, Kazuki; Akai, Shuji (Synlett, 2012)
Complementary synthesis of two kinds of fluorinated bridged biphenyls has been developed by the combination of oxidative carbon–carbon bond formation and deoxyfluorination.
Keywords: fluorine; deoxyfluorination; biaryls; umpolung; hypervalent iodine